Ultrasound-Assisted Intraosseous Injection of Platelet-Rich Plasma for a Patient With Tibial Plateau Subchondral Bone Marrow Lesion: A Case Presentation and Technical Illustration - Lam, King Hei Stanley (Cureus, 2020)
The subchondral bone marrow lesion (BML) has been found to have a significant correlation with pain in osteoarthritis patients. The intraosseous injection with orthobiologics such as platelet-rich plasma (PRP) or bone marrow aspirate concentrate has shown a promising therapeutic effect on BML-related pain. Traditionally, the intraosseous injection was performed with a large caliber trocar to break into the subchondral bone under fluoroscopy guidance and the patient was usually sedated prior to the procedure. In this report, we presented a 55-year-old woman who suffered from refractory right lateral knee pain for three months. The MRI revealed a right lateral tibial plateau subchondral BML, tears of medial and lateral menisci, and a general osteoarthritic appearance. We used ultrasound (US) to guide a 21-gauge needle through a pre-existing cortical break on the Gerdy’s tubercle for the intraosseous PRP injection. The contrast was confirmed to reach the subchondral bone of the lateral tibial plateau and the injection reproduced the patient's symptoms. Three weeks later, the patient had significant improvement in the visual analog scale and function. In conclusion, intraosseous injection with PRP is a possibly effective treatment for subchondral BML in knee osteoarthritis, and US can facilitate a smaller gauge needle placement without the need to sedate the patient.